2019
DOI: 10.1111/1748-5967.12404
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feed materials on the nutrient composition of Protaetia brevitarsis larvae

Abstract: To find out the effect of feed materials on the nutrient composition of Protaetia brevitarsis larvae (Pbl), three different feed materials were prepared and fed to the Pbl populations. After the Pbl population reached the third instar stage, they were boiled and dried for the nutrient analysis. The results showed that the nutrient composition of Pbl varied in response to the feed materials. Therefore, it is critical to set a feed material standard to guarantee the efficacy of Pbl medicinal property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This species is diurnal and univoltine, and its third instar larval stage is found in the soil during winters (Zhang 1984). Furthermore, P. brevitarsis larvae are edible insects, consumed in Asian countries as an important food supplement because of their high nutritional value, such as high protein (42.5-57.9%), fat (7.3-26.7%), and carbohydrate (10.5-23.7%) content, as well as for their antioxidative, anticancer, antiobesity, antidiabetic, and hepatoprotective effects (Ghosh et al 2017;Jeong et al 2020;Kim et al 2021;Lee et al 2017;Sung et al 2016). The United Nations' Food and Agriculture Organization (FAO) has highlighted the need to develop novel and sustainable protein sources in response to the continued worldwide population expansion, which is projected to reach nine billion by 2050, and edible insects are being explored as a potential alternative protein source (Van Huis 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This species is diurnal and univoltine, and its third instar larval stage is found in the soil during winters (Zhang 1984). Furthermore, P. brevitarsis larvae are edible insects, consumed in Asian countries as an important food supplement because of their high nutritional value, such as high protein (42.5-57.9%), fat (7.3-26.7%), and carbohydrate (10.5-23.7%) content, as well as for their antioxidative, anticancer, antiobesity, antidiabetic, and hepatoprotective effects (Ghosh et al 2017;Jeong et al 2020;Kim et al 2021;Lee et al 2017;Sung et al 2016). The United Nations' Food and Agriculture Organization (FAO) has highlighted the need to develop novel and sustainable protein sources in response to the continued worldwide population expansion, which is projected to reach nine billion by 2050, and edible insects are being explored as a potential alternative protein source (Van Huis 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, about 2000 species of edible insects, mainly beetles, caterpillars, bees, wasps, grasshoppers, crickets, and flies, are known worldwide [ 8 , 9 ]. Since studies on the extraction and efficacy of various substances from various potential and already licensed edible insects are being conducted, the number of food and pharmaceutical raw materials obtained from insects is expected to increase in the future [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, various physiological benefits of the P. brevitarsis larvae, such as antioxidant, antibacterial, anticancer, and antithrombotic effects, have been already proven scientifically ( Lee et al, 2017 ; Yoon et al, 2003 ). With the registration of P. brevitarsis larvae as a general food ingredient, recent studies have noted that of the proximate composition of P. brevitarsis larvae varied considerably: moisture (3.99%–7.98%), protein (42.46%–57.86%), fat (7.33%–26.70%), ash (3.96%–8.45%), and carbohydrate (10.56%–23.71%) ( Chung et al, 2013 ; Ghosh et al, 2017 ; Jeong et al, 2020 ; Kim et al, 2017 , Yeo et al, 2013 ). Regarding the large variation in proximate composition, Choi et al (2019) have suggested that the nutritional composition of the P. brevitarsis larvae could be affected by feeding sources, similarly to conventional livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to establish a potentially applicable production system, it could be primarily necessary to compare the nutritional composition of edible insects produced by various current production systems. Until now, although there are some previous studies determining the nutritional composition of P. brevitarsis larvae ( Chung et al, 2013 ; Ghosh et al, 2017 ; Jeong et al., 2020 ; Kim et al, 2017 ; Yeo et al, 2013 ), but little studies have been compared the nutritional composition of P. brevitarsis larvae produced from different commercial farms. Therefore, the objective of this study was to determine the major nutritional composition (proximate composition, amino acid profile, and fatty acid profile) of white-spotted flower chafer ( P. brevitarsis ) larvae, collected from five commercial insect farms in Korea.…”
Section: Introductionmentioning
confidence: 99%